Besnoitiosis in bulls in Portugal - Cortes, Helder Carola Espiguinha (2005)
BOVINE besnoitiosis is caused by Besnoitia besnoiti, a coccidial protozoan (Fayer 1981, Tadros and Laarman 1982). Animals of all ages may be affected, but clinical disease is unusual in calves younger than six months of age (Bigalke 1968). The disease usually occurs sporadically, and most infections are subclinical (Pols 1960, Bigalke 1968).